2017
DOI: 10.1016/j.cub.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Influence on Eye Movements to Complex Scenes at Short Timescales

Abstract: Summary Where one looks within their environment constrains one’s visual experiences, directly affects cognitive, emotional, and social processing [1–4], influences learning opportunities [5], and ultimately shapes one’s developmental path. While there is a high degree of similarity across individuals with regard to which features of a scene are fixated [6–8], large individual differences are also present, especially in disorders of development [9–13], and clarifying the origins of these differences are essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 35 publications
7
96
2
Order By: Relevance
“…But it probably also reflects a deep-rooted neurobiological basis of these biases. This possibility is underscored by earlier studies showing that the visual salience of social stimuli is reduced in individuals with autism spectrum disorder 27,38,39 and most importantly by recent twin studies, showing that individual differences in gaze traces are heritable 27,28 . The gaze trace dissimilarities investigated in these studies probably are a manifestation of the salience biases we found here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But it probably also reflects a deep-rooted neurobiological basis of these biases. This possibility is underscored by earlier studies showing that the visual salience of social stimuli is reduced in individuals with autism spectrum disorder 27,38,39 and most importantly by recent twin studies, showing that individual differences in gaze traces are heritable 27,28 . The gaze trace dissimilarities investigated in these studies probably are a manifestation of the salience biases we found here.…”
Section: Discussionmentioning
confidence: 99%
“…However, even the earliest studies of fixation behaviour noted considerable individual differences 19,20 , and basic occulomotor traits vary reliably between observers [21][22][23][24][25][26] . Recent twinstudies revealed that social attention and gaze traces across complex scenes are highly heritable 27,28 . This suggests individual differences in fixation behaviour are not random, but systematic.…”
Section: Introductionmentioning
confidence: 99%
“…We further calculated the eye movement entropy as an index to quantify how strategical children with ASD was to process human faces compared to TD children. First, each valid trial duration heatmap was produced by smoothing gaze data using a 2° full width at half maximum (FWHM) Gaussian kernel spatial filter (Kennedy et al, ). For each child, their all valid trial smoothed duration heatmaps were averaged together to produce two mean heatmaps (one for each condition).…”
Section: Methodsmentioning
confidence: 99%
“…For each child, their all valid trial smoothed duration heatmaps were averaged together to produce two mean heatmaps (one for each condition). Then, Shannon entropy was calculated on the mean heatmaps (Gu et al, ; Kennedy et al, ). Entropy provides a measure of statistical randomness or agglomeration of the participants’ eye movements, such that spatially diffused gaze would result in higher entropy values, and spatially tightly focused gaze would result in lower entropy values (Figures and in the supplementary material).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation